Transgene Biocontainment Strategies for Molecular Farming - Clark, Michael; Maselko, Maciej (Frontiers in Plant Science, 2020)
Advances in plant synthetic biology promise to introduce novel agricultural products in the near future. ‘Molecular farms’ will include crops engineered to produce medications, vaccines, biofuels, industrial enzymes, and other high value compounds. These crops have the potential to reduce costs while dramatically increasing scales of synthesis and provide new economic opportunities to farmers. Current transgenic crops have been repeatedly demonstrated to be safe, however, molecular farming may generate plants where there are legitimate concerns of risks to human health and the environment. Unwanted gene flow from engineered crops may contaminate the food supply, affect wildlife, and limit growth of this agricultural sector. Unwanted gene flow into engineered crops may alter their ability to produce compounds of interest and potentially result in harmful impurities. Here we review potential applications of molecular farming and the various genetic and physical methods for transgene biocontainment. As yet, no technology can be applied to all crop species, such that a combination of approaches may be necessary. It is clear that effective biocontainment will be needed to ensure the safety of field grown molecular farming crops.